Design of an optimal micro direct methanol fuel cell for portable applications - M.M. Ahmad,; S.K. Kamarudin,; W.R.W. Daud, (Universiti Kebangsaan Malaysia, 2010)
The main constraint for the commercialization of micro Direct Methanol Fuel cell (μDMFC) for small power generation is the performance of the fuel cell. In this study, a high-power μDMFC with a power output of 14.10 mW on an active area of 4 cm2 and catalyst loading of 0.5 mg cm-2 cathode was successfully developed. The optimal parameters for methanol concentration and catalyst loading were determined. Besides that, testing of performance, long term and open circuit voltage (OCV) was also performed.